PERAN BHABINKAMTIBMAS DALAM PENCEGAHAN CURANMOR - anggio pratama anggio (Advances in Police Science Research Journal, 2020)
The phenomenon that happened in the community these days, with the high number of unemployment, however the needs of everyday life can influence the way of thinking, and to act on community that impacted the criminality action, for example theft crime. One of the examples of rampant theft cases in Indonesia is the case of motor vehicle theft. For the Majalengka Police Resort jurisdiction, based on the data recorded in 2018 there are 178 cases of motor vehicle theft and in 2019 there are 271 cases of motor vehicle theft. Binmas works to prevent and solve the problems by prioritizing preventive communications by conducting a counseling aims to increase the awareness of community regarding to the law to create a proactive community in the realization of conducive situation. The purpose of this research is to give description, to analyze the implementation of counseling and to analyze factors that influenced the counseling activity by Bhabinkamtibmas in the Majalengka Police Resort jurisdiction. This research used a qualitative approach with analysis descriptive research. The research’s location is Majalengka Police Sector. The data collection techniques used are interview, observation and documents study methods. The data validity used in this research are transformability, confirmability, triangulation and data credibility. The research results showed that the efforts made by Bhabinkamtibmas in preventing the motor vehicle theft in the Majalengka Police Sector have been running optimally analyzed using the management theory by George R. Terry. The external factors that influenced the implementation of Bhabinkamtibmas members are the availability of adequate budget and the right chosen method, whereas the internal factors are the education of Bhabinkamtibmas members, where many of the Bhabinkamtibmas members of Majalengka Police Sector have not attend the vocational education and the lacks of total placement of fostered areas. When viewed from the infrastructure obtained by Bhabinkamtibmas in implementing the activity in the fostered areas are still lacking.